Characterization and effect of clarified araçá (Psidium guineenses Sw.) juice on postprandial glycemia in healthy subjects - Balisteiro,Diully Mata (2013)
Brazilian native fruits are excellent sources of bioactive compounds of phenolic nature. Some of these compounds are able to inhibit carbohydrate- metabolizing enzymes (in vitro), α-amylase and α-glucosidase, delaying carbohydrate digestion. This study aimed to evaluate the effect of clarified araçá (Psidium guineenses Sw.) juice on postprandial glycemia in humans after consumption of 25 g of available carbohydrates (approximately 50 g of white bread) and characterize the phenolic compounds and in vitro antioxidant capacity of araçá juice and pulp. The results showed that the clarified juice had a positive effect on postprandial glycemia reducing the total amount of glucose absorbed, lengthening the time to reach maximum blood glucose concentration, reducing glucose incremental velocity, and decreasing glucose incremental percentage. Both frozen pulp and clarified juice had high amounts of phenolic compounds, antioxidant capacity, and proanthocyanidins, among which oligomers (monomers to tetramers), pentamers, hexamers, heptamers, octamers, nonamers, decamers, and polymers were detected, and they are probably associated with in vivo effects.